Kain Batik Ciprat Kreasi Wisnuwardhana (Teknik Ciprat dan Oles) - Wahyulina, Diah; Chrisdanty, Febry (Jurnal ABM Mengabdi, 2024)
This type of batik making is not only done by canting, but is also known as splashed batik. Sprinkled batik is unique in its motif, where the motif is formed with different patterns depending on the tapa style used to splash. All the abstract splash patterns make this splashed batik different from other batik. To be able to produce products in the form of splashed batik applications, partners need assistance and guidance to carry out the steps in making splashed batik, which will then be used as material to make finished products that are ready to use and ready to be marketed for general sale. This training in making splashed batik creations is carried out with several types of training, namely starting with theoretical training, after that it will continue with practical training where partners will directly make splashed batik. The application of splashed batik is the basic material for making ready-to-wear products such as t-shirts and other types of clothing. This training program is held to develop partners' skills and can be used as business capital for partners to provide additional income for their families